Class Analysis and Social Transformation - Savage M. Mike (Sociology and social change)
Academic discussions about social class tend to be increasingly specialized and have found it difficult to unpack processes of cultural as well as social change. This book breathes new life into class analysis by showing how contemporary social and cultural transformations are related to the restructuring of class relations. Using the British experience as a case study, Mike Savage gives a definitive account of debates on class and finds evidence of both the breaking down and persistence of class divisions. He employs a variety of disciplinary perspectives to provide a comprehensive account of the main features of contemporary social change. Particular attention is paid to arguments developed by Beck and Giddens concerning individualization, and he shows how the redrawing of individual relations is tied in to the remaking of social class in complex and largely unrecognized ways. Class Analysis and Social Transformation brings together recent empirical research on class with topical theoretical debates on social and cultural change. It offers a compelling interpretation of the field in its entirety and an authoritative and accessible text for social science students wishing to learn about the debates on class analysis.